Wielowymiarowa analiza porównawcza stopnia dynamicznego zharmonizowania rozwoju społecznego i gospodarczego krajów - Wydymus, Stanisław (Wydział Prawa i Administracji UAM, 1986)
The purpose of the article is to present several analitical proposals concerning the study of the degree of dynamic harmonization of social and economic development in particular countries and in homogenous groups of such countries. The basis for such an analysis is the assumption in countries with balanced structure of social and economic development the rate of the development of economic potential is similar to the rate of the development of consumption "sensu largo". The research proposals submitted in the article employ several algorithms belonging to the multidimensional comparative analysis. They have been applied in the empirical part of the work, concerning study of the degree of harmonization of social and economic development in several tens of countries divided — by taxometric methods — into 3 groups with different levels of development in each of them. The results of the research allowed, among others., to reach the conclusion about the ex listen ce of the connection between the degree of the said harmonization and the level of social and economic development. Moreover, the above conclusion is of the character of general regularity of development of the entire system of world economy.
Multidimensional Comparative Analysis of the Degree of Dynamic Harmonization of Social and Economic Development of Coutries